2018
DOI: 10.1085/jgp.201711860
|View full text |Cite
|
Sign up to set email alerts
|

The N terminus of α-ENaC mediates ENaC cleavage and activation by furin

Abstract: Epithelial Na channels comprise three homologous subunits (α, β, and γ) that are regulated by alternative splicing and proteolytic cleavage. Here, we determine the basis of the reduced Na current (I) that results from expression of a previously identified, naturally occurring splice variant of the α subunit (α-ENaC), in which residues 34-82 are deleted (α). α-ENaC expression with WT β and γ subunits in oocytes produces reduced basal I, which can largely be recovered by exogenous trypsin. With this α-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In fact, the assertion that the FCS in SARS-CoV-2 has an unusual, nonstandard amino acid sequence is false. The amino acid sequence of the FCS in SARS-CoV-2 also exists in the human ENaC α subunit ( 16 ), where it is known to be functional and has been extensively studied ( 17 , 18 ). The FCS of human ENaC α has the amino acid sequence RRAR'SVAS ( Fig.…”
Section: Overlooked Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the assertion that the FCS in SARS-CoV-2 has an unusual, nonstandard amino acid sequence is false. The amino acid sequence of the FCS in SARS-CoV-2 also exists in the human ENaC α subunit ( 16 ), where it is known to be functional and has been extensively studied ( 17 , 18 ). The FCS of human ENaC α has the amino acid sequence RRAR'SVAS ( Fig.…”
Section: Overlooked Detailsmentioning
confidence: 99%
“…ENaC is an epithelial sodium channel, expressed on the apical surface of epithelial cells in the kidney, colon, and airways ( 19 , 20 ), that plays a critical role in controlling fluid exchange. The ENaC α subunit has a functional FCS ( 17 , 18 ) that is essential for ion channel function ( 19 ) and has been characterized in a variety of species. The FCS sequence of human ENaC α ( 20 ) is identical in chimpanzee, bonobo, orangutan, and gorilla ( SI Appendix , Fig.…”
Section: Overlooked Detailsmentioning
confidence: 99%
“…The effects of the extended cytosolic NH2-terminal tail for the δ 802 -ENaC are unknown. The N-terminal tails of α, β, and γ-ENaC subunits are involved in endocytosis-related channel activity 53, 54, PIP2 binding and hydrolysis 55, 56, intracellular gating 57, 58, interaction with CFTR 31, and proteolysis 14, 59, 60. By comparing of δ 1 βγ and δ 2 βγ channels in oocytes, it was found that δ 2 channels had an increased single channel conductance and activity 29.…”
Section: Discussionmentioning
confidence: 99%
“…This near-identical furin site enhances SARS-CoV-2 cleavage for replication [104,106] and implies competition between it and the hosts' αENaC in endosomes for furin-mediated cleavage. Furin is a physiological activator of ENaC [108]. In the absence of furin, ENaC is cleaved on different sites [118,119] by extracellular proteases, including channel-activating protease (CAP1) [120], CAP2/TMPRSS4, CAP3/matriptase, and plasmin [119] (reviewed in [55]), resulting in overactive ENaC.…”
Section: Structural Site Of Sars-cov-2 and Hyperactivation Of Enacmentioning
confidence: 99%